The Influence Of Customer Commitment, Halal Awareness, And Perceived Value On Repurchase Intention Of Coto Makassar - Dinda Nada Kamilah; Nurul Asmi; Ahmad Nuh (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study explores how customer perceived value (CPV), commitment, and awareness of halal standards affect Muslim consumers' repurchase intentions. CPV represents consumers' evaluation of benefits versus costs, with a focus on fostering loyalty and repeated purchases, especially for halal certified items. The research also emphasizes halal awareness, as understanding halal principles influences Muslim consumers' buying decisions. Using a quantitative methodology, the study confirms that CPV strongly impacts both customer commitment and repurchase intention. Additionally, it reveals a significant link between halal awareness and repurchase intention, underscoring the need for businesses to enhance CPV, commitment, and halal education to build loyalty and encourage repeat buying behavior.